Organocatalytic Enantioselective Nitro-Vinylcyclopropane-Cyclopentene Rearrangement: Expanding the Reactivity of Donor–Acceptor Cyclopropanes - García, Lorena; Carrillo, Luisa; Reyes, Efraím; Uria, Uxue; Prieto, Liher; Vicario, Jose L. (Synthesis, 2025)
The catalytic enantioselective rearrangement of nitro-vinylcyclopropylacetaldehydes has been studied using chiral secondary amines as catalysts. The reaction proceeds through the in situ generation of a donor–acceptor cyclopropane, which rearranges to the corresponding cyclopentene through an open conjugated iminium/unsaturated nitronate intermediate, where the stereochemistry of the starting cyclopropane is lost. This intermediate undergoes an intramolecular Michael reaction in which the asymmetric induction provided by the catalyst allows the preparation of substituted nitrocyclopentenes in good yields and with high stereocontrol. The obtained 2-nitrocyclopentenylacetaldehydes have been transformed into valuable chiral cyclopentenones through Nef reaction with complete retention of the stereochemical information.
Keywords: Enantioselective; Organocatalysis; Rearrangement; Vinylcyclopropane; Cyclopentene; Donor–acceptor cyclopropane; Aldehyde; Nitroolefine